Generalized Analytic Fourier-Feynman Transform of Functionals in a Banach Algebra ℱA1,A2a,b - Jae Gil Choi; David Skoug; Seung Jun Chang (Journal of Function Spaces and Applications)
We introduce the Fresnel type class ℱA1,A2a,b. We also establish the existence of the generalized analytic Fourier-Feynman transform for functionals in the Banach algebra ℱA1,A2a,b.